Atlas of Robotic Prostatectomy - John, Hubert; Wiklund, Peter; Witt, Jorn H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
In many centers of excellence in Urology, robotic prostatectomy has become the first choice for the surgical treatment of localized prostate cancer owing to benefits such as reduced pain and minimization of impotence and incontinence. This atlas, specifically designed for use by surgeons, provides a beautifully illustrated, step-by-step guide to all aspects of the procedure. The various techniques that can be employed to achieve excellent oncological and functional results are carefully depicted in appropriate detail; for example, nerve-sparing techniques, bladder neck reconstruction, and approaches aimed at the early restoration of continence are clearly described. Special situations, such as prior prostate surgery, a large prostate, and salvage prostatectomy, are also fully covered. The information contained in this atlas will be of great value in enabling surgeons to improve their results and to take full advantage of the benefits of robotic prostatectomy compared with open prostatectomy.
Anatomy -- Screening and diagnosis -- Anesthesiology -- Instruments -- Port placement -- Retropubic space -- Lymphadenectomy -- Endopelvic fascia -- DVC/Santorini's plexus -- Puboprostatic ligaments -- Bladder neck dissection -- Vas, seminal vesicle -- Retroprostatic dissection -- Prostate columns -- Neurovascular bundle -- Apical dissection -- Bladder neck reconstruction -- Anastomotic techniques -- Additional approaches for functional restoration -- Complications.
Keywords: Medicine; Surgery; Urology; Medicine & Public Health; Urology/Andrology.; General Surgery